Microbial safety of fresh produce - Fan, Xuetong (The IFT Press series)
Microbial Safety of Fresh Produce covers all aspects of produce safety including pathogen ecology, agro-management, pre-harvest and post-harvest interventions, and adverse economic impacts of outbreaks.